Model Satellite Design for CanSat Competition - Bulut, Sultan Nur; Gül, Mahircan; Beker, Can; İpek, İbrahim İlge; Koculu, Ömer Eren; Topaloğlu, Çınar; Dinçer, Nurullah; Kirli, Ahmet; Ertuğrul, Hasan Fatih; Tüfekçi, Celal Sami (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
Objective of this work is to design and manufacture a model satellite named Vecihi that is able to perform some of the basic tasks that artificial satellites perform. The satellite is developed under the rules of CanSat Competition 2013, which aims to promote innovative space solutions and to improve the current systems. The Vecihi satellite designed around budgetary, dimensional, and mass requirements as set in the competition guidelines, while carrying and landing its payload successfully.
Keywords: Model Satellite; CanSat; Aero Breaking; Telemetry Transmission